Flavanone Intake Is Inversely Associated with Risk of Incident Ischemic Stroke in the REasons for Geographic and Racial Differences in Stroke (REGARDS) Study. Issue 11 (21st September 2016) - Goetz, Margarethe E; Judd, Suzanne E; Hartman, Terryl J; McClellan, William; Anderson, Aaron; Vaccarino, Viola
Abstract: Background: Flavonoids may have beneficial cerebrovascular effects, but evidence from racially and geographically representative cohorts in comprehensive flavonoid databases is lacking. Given racial and geographic disparities in stroke incidence, representative cohort studies are needed. Objectives: We evaluated the association between flavonoid intake and incident ischemic stroke in a biracial, national cohort using updated flavonoid composition tables and assessed differences in flavonoid intake by sex, race, and region of residence. Methods: We evaluated 20, 024 participants in the REGARDS (REasons for Geographic and Racial Differences in Stroke) study, a biracial prospective study. Participants with stroke history or missing dietary data were excluded. Flavonoid intake was estimated by using a Block98 food frequency questionnaire and the USDA's Provisional Flavonoid Addendum and Proanthocyanidin Database. Associations between quintiles of flavonoid intake and incident ischemic stroke were evaluated by using Cox proportional hazards models, adjusting for confounders. Results: Over 6.5 y, 524 acute ischemic strokes occurred. Flavanone intake was lower in the Southeastern United States but higher in blacks than in whites. After multivariable adjustment, flavanone intake was inversely associated with incident ischemic stroke (HR: 0.72; 95% CI: 0.55, 0.95; P -trend = 0.03). Consumption of citrus fruits and juices was inversely associated with incident ischemic stroke (HR: 0.69; 95% CI: 0.53, 0.91; P -trend = 0.02). Total flavonoids and other flavonoid subclasses were not associated with incident ischemic stroke. There was no statistical interaction with sex, race, or region for any flavonoid measure. Conclusions: Greater consumption of flavanones, but not total or other flavonoid subclasses, was inversely associated with incident ischemic stroke. Associations did not differ by sex, race, or region for the association; however, regional differences in flavanone intake may contribute to regional disparities in ischemic stroke incidence. Higher flavanone intake in blacks suggests that flavanone intake is not implicated in racial disparities in ischemic stroke incidence.